ANALISIS IMPLEMENTASI CONTRACTOR SAFETY MANAGEMENT SYSTEM (CSMS) PADA TAHAP PERSIAPAN KERJA DI COCA COLA AMATIL INDONESIA (CCAI) SEMARANG - Suery, Zainal Abidin; Kurniawan, Bina; Ekawati, Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Contractor Safety Management System (CSMS) is a system for managing occupational health and safety (OHS) of contractor in site of business. Work performace by contractor has three category levels of category is low category, medium category and high category. Base on accidently data in Coca Cola Amatil Indonesia (CCAI), there are four fatality incident were recorded in 2013 and three fatality incident in 2014 suffered by contractor. The implementation of CSMS in CCAI still there is unconformity in the implementation. Especialy on OHS requirement compliance by contractor. The OHS requirement compliance by contractor must be completed on pre-job phase. The Iplementation of CSMS on pre-job phase can be affected by variabels such bureaucratic structural, communication, resource, and dispotition of implementor. The purpose of this study is to analyze the implementation of CSMS in pre-job phase in CCAI Semarang. This research is a descriptive study with qualitative approach is done by in-depth interviews. The subjects of this study consists of two main informants and three triangulation informants. The results showed most of the implementation of CSMS in pre-job phase are progressing well. Can be shown from there is procedure for managing, the clearness of communication in each of event, and the dispotation of CCAI management that fully supported for CSMS implementation. But still there is unconformity in the system of document requirement compliance by contractor. There is no defference in form/application of reqqquirement compliance document for all contractors. Where generalized for all contractors. it should be distinguished form/application of requirement compliance document for each contractor.